Development of People's Economy Based on Traditional Values in Bali - I Wayan Rideng; Ketut Kasta Arya Wijaya; Wayan Suarjana (Law Doctoral Community Service Journal, 2023)
Economic growth in a country is crucial for the well-being of its society. This research utilizes the normative research method, which is a scientific research method to discover truths based on scholarly logic from a normative perspective. Legal materials in normative research can include primary legal sources, secondary legal sources, and non-legal sources. The results of this research explain that various forms of institutions have been established in efforts to develop the community's economy at the village level, such as Village-Owned Enterprises (BUM Desa) and Cooperatives, as mandated by Law Number 6 of 2014 concerning Villages.